Comparative study of accuracy and clinical agreement of the CoaguChek XS portable device versus standard laboratory practice in unexperienced patients - Torreiro, Eduardo G.; Fernández, Elizabeth Gómez; Rodríguez, Rosa Mariño; López, Carmen Vázquez; Núñez, Julia Barreal (Thrombosis and Haemostasis, 2009)
The objective of the study was to compare the accuracy and clinical agreement of the CoaguChek XS versus the standard laboratory practice. Forty-one patients on long-term anticoagulation with acenocumarol without previous experience in self-monitoring participated to obtain 218 pairs of data. Several methods for comparative statistics were applied to assess the possible disagreements between techniques as well as a range of previously published criteria of clinical agreement and the very recently described error-grid for INR comparison that we partially modify. The mean age was 52.1 and the indications for oral anticoagulation were prosthetic valves (36.59%), atrial fibrillation (34.15%), venous thromboembolic disease (21.95%) and others (7.31%) with a target range of 2–3 INR units (63.4%) or 2.5–3.5 (36.6%). Analyzing the whole series of data, the Pearsons ρ correlation coefficient for precision between methods was 0.95 and the Cb bias correction factor for accuracy 0.99 with a minimal bias of 0.1 INR units between methods applying the Bland-Altman plot. The linear regression procedure described by Passing and Bablok showed a minimal deviation from the best-fit line and a slope of 0.90. The mean of the absolute relative differences was 7% which is in the “very good” range of agreement. No results were found in the clinically “dangerous” D zone of the error-grids with 99% of data in the clinically irrelevant and low relevant areas A and B. In this study self-management with the CoaguChek XS was clinically safe and reliable.
Keywords: Self-management; oral anticoagulation; CoaguChek XS; acenocumarol; INR